Metaformose das metamorfoses: Leminski reinventa Ovídio - Pereira, Lívia Mendes [UNESP]; Vieira, Brunno Vinicius Gonçalves [UNESP] (My University, 2014)
This article provides an analysis of Leminski’s Metaformose that establishes a remarkable re-reading of Ovid’s Metamorphoses. It is a poetic narrative published posthumously in 1994. * is work, which received “Prêmio Jabuti de Poesia” in 1995, was found among the papers of the author along with many essays, short stories, poems and a novel. * rough the author’s own theoretical conceptions, one seeks to interpretating the way the myth of Arachne is approached by him, re' ecting on the reinvention and reinterpretation of both Greek and Latin mythology and Literature in contemporary writing.

Este artigo oferece uma análise da obra Metaformose de Paulo Leminski que estabelece uma singular releitura das Metamorfoses de Ovídio. Trata-se de uma narrativa poética publicada como obra póstuma no ano de 1994. Encontrado entre os papéis do autor juntamente com diversos ensaios, contos, poemas e uma novela, recebeu o “Prêmio Jabuti de Poesia” no ano de 1995. Por meio das próprias concepções teóricas do autor, busca-se interpretar a maneira como é tratado o mito de Aracne, re' etindo sobre a reinvenção e releitura da Mitologia e da Literatura greco-latinas na escrita contemporânea.
Metaformose of metamorphoses: Leminski reinvents Ovid
Keywords: Ovid; Paulo Leminski; reception of Greek and Latin Literature; Ovídio; Leminski; Recepção da Literatura Clássica